Prevalence of targetable genomic alterations among a diverse population participating in the ASCO TAPUR Study - Pam K. Mangat; M. Kelsey Kirkwood; Dominique C. Hinshaw; Elizabeth Garrett-Mayer; Richard L. Schilsky (npj Precision Oncology)
Abstract The Targeted Agent and Profiling Utilization (TAPUR) Study (NCT02693535, registered on February 23, 2016) is a phase II basket trial evaluating the antitumor activity of commercially available targeted agents in patients with advanced cancers harboring genomic alterations known to be drug targets. We analyzed the prevalence of targetable gene alterations in the diverse population of patients participating in this study. We assessed 978 gene alterations or other biomarkers across sex, age, race, ethnicity, BMI category, smoking status, Eastern Cooperative Oncology Group performance status, and cancer type in 3448 registrants. We report a higher prevalence of genomic targets of FDA-approved therapies for various cancers, including PDGRFA in Hispanic versus non-Hispanic registrants and JAK2 in Asian versus White registrants. This study reinforces the importance of recruiting diverse populations of patients to clinical trials and provides evidence that may inform the development of strategic treatment plans that consider patient demographics in addition to tumor characteristics. Clinicaltrials.gov NCT02693535.